Health trajectories across the work exit transition in the 1990s, 2000s, and 2010s: the role of working conditions and policy - Maaike van der Noordt; Theo G. van Tilburg; Suzan van der Pas; Bram Wouterse; Dorly J. H. Deeg (BMC, 2023)
Abstract Purpose We examined health trajectories of Dutch older workers across their exit from the workforce in the 1990s, 2000s, and 2010s, testing the hypothesis that pre-post-exit health trajectories of workers with favourable and unfavourable working conditions increasingly diverged over time due to policy measures to extend working life. Methods The Longitudinal Aging Study Amsterdam includes baseline samples in 1992/1993, 2002/2003 and 2012/2013 with two 3-year follow-up waves each. Selected respondents were aged 55 years and over who exited from a paid job within the first or second 3-year interval, up to and including the statutory retirement age (N = 522). Pre-post-exit trajectories were modelled using Generalized Estimating Equations with outcomes self-rated health and physical limitations and determinants physical demands, psychosocial demands, and psychosocial resources. Results Average work exit age rose from 60.7 in the 1990s to 62.9 in the 2010s. On average, self-rated health decreased somewhat over successive periods and did not show pre-post-exit change; average physical limitations increased substantially both over successive periods and from pre- to post-exit. No support is found for our hypothesis. However, regardless of work exposures, we found sharp pre-post-exit increases in physical limitations in the 2010s. Conclusion Although these findings provide no support for our hypothesis of diverging health trajectories over time based on work exposure, they show that exiting at a higher age is linked to poorer pre- and post-exit health and to pre-post-exit increases in physical limitations, suggesting greater health care costs in the near future.